2019
DOI: 10.1037/pha0000272
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cannabidiol on alcohol-related outcomes: A review of preclinical and human research.

Abstract: Increased access to medicinal and recreational cannabis will be accompanied by greater exposure to its chemical constituents, including Δ9-tetrahydrocannabinol (Δ9-THC) and cannabidiol (CBD), the primary nonpsychoactive compound. Increasing attention has focused on CBD, in part, due to its potential therapeutic properties. Relatively little is known about how CBD might interact with other commonly used drugs. While a number of studies have explored the influence of cannabis or Δ9-THC on alcohol consumption and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 82 publications
2
19
0
Order By: Relevance
“…CBD has been also shown to be effective for neuropsychiatric disorders including substance use disorders (SUDs) [16][17][18][19][20]. There is a number of articles that have reviewed recent research regarding CBD actions against psychostimulants [17,20], opioids [21,22], ∆ 9 -THC [23] and alcohol [24,25] in both humans and experimental animals. However, the majority of them focus on experimental evidence supporting or refuting the use of CBD for the treatment of SUDs, while little attention has been given to recent research regarding the possible receptor mechanisms underlying CBD's action in different animal models of drug abuse and addiction.…”
Section: The History Of Medicinal Cannabidiolmentioning
confidence: 99%
“…CBD has been also shown to be effective for neuropsychiatric disorders including substance use disorders (SUDs) [16][17][18][19][20]. There is a number of articles that have reviewed recent research regarding CBD actions against psychostimulants [17,20], opioids [21,22], ∆ 9 -THC [23] and alcohol [24,25] in both humans and experimental animals. However, the majority of them focus on experimental evidence supporting or refuting the use of CBD for the treatment of SUDs, while little attention has been given to recent research regarding the possible receptor mechanisms underlying CBD's action in different animal models of drug abuse and addiction.…”
Section: The History Of Medicinal Cannabidiolmentioning
confidence: 99%
“…10 In the alcohol research field, to date, CBD has been tested in a limited number of preclinical studies. 11,12 Specifically, acute and/or repeated treatment with CBD attenuated (i) context-and stress-induced reinstatement of alcohol seeking in rats, 13 (ii) alcohol drinking in mice exposed to the ''alcohol versus water'' choice regimen, 14 (iii) binge-like drinking in mice exposed to the ''drinking-in-the-dark'' procedure, 15 and (iv) operant oral alcohol self-administration in mice. 14,16 It is therefore of interest to test CBD in additional animal and experimental models of AUD, with the intent of better characterizing its ''antialcohol'' potential before possibly moving to clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it may be interesting to test whether these compounds are a therapeutic target to increase resilience to the effects of stress on drug addiction. Among these compounds, we would highlight cannabidiol, which is effective in reducing PTSD[ 272 ] and the effects of cocaine and other drugs of abuse[ 273 , 274 , 275 ]. A recent study in our laboratory demonstrated that cannabidiol prevents the stress-induced reinstatement of cocaine CPP[ 154 ].…”
Section: Future Research Directionsmentioning
confidence: 99%